Kompetensi Kerja dan Kinerja Pemeriksaan Kapal: Bukti Empiris Kelaiklautan Kapal di Indonesia - Latifah, Alfi; Sitorus, Marthaleina Ruminda; Thamrin, Muhammad; Agusinta, Lira; Sugiyanto, Sugiyanto (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2024)
The main problems of this research, namely work competency, training of marine inspectors, ship inspection performance on the seaworthiness of ships in Indonesia have not contributed optimally and optimally. This research aims to analyze the direct and indirect contribution to the work competency, training of marine inspectors through ship inspection performance on the seaworthiness of ships in Indonesia. The research method uses path analysis for direct contributions and to determine indirect contributions using the Sobel test. The sample of this research consisted of 60 people who were maritime inspector education and training participants who were currently taking part in marine inspector training at the maritime transportation training center. The research findings state that there is a direct contribution from work competency and training of marine inspectors to ship inspection performance, but there is no direct contribution from work competency to ship seaworthiness. Meanwhile, training of marine inspectors and ship inspection performance contribute directly to the seaworthiness of ships. Ship inspection performance contributes and is able to function as an indirect mediator of work competency and training of marine inspectors on ship seaworthiness.